Filling the gaps: Advancing neglected and underutilised species and knowledge systems in Thailand for food security and environmental sustainability - Saiyasombat, Worakrit; Chathiran, Wimonphan; Chimasangkanan, Jaruwan; Bromage, Sabri; Borelli, Teresa; Hunter, Danny; Srichamnong, Warangkana (Roskilde University, 2025)
Neglected and underutilised species (NUS) offer potential to enhance nutrition, food security, and environmental sustainability. Of the over 30,000 edible plant species that exist globally, fewer than 150 are commercially cultivated, accelerating the loss of agrobiodiversity and the homogenisation of food systems. Using Thailand as a case study, this review highlights five NUS—yellow burrhead (Limnocharis flava Buch.), Ceylon oak (Schleichera oleosa (Lour.) Merr.), bastard oleaster (Elaeagnus latifolia L.), star apple (Chrysophyllum cainito L.) and hogweed (Physalis angulata var. angulata)—for their high nutritional and medicinal potential. These species can diversify diets, promote sustainable agriculture, and revive indigenous food cultures, but their adoption is hindered by limited infrastructure, low consumer awareness, and insufficient inclusion in food composition databases. Integrating NUS into these databases supports accurate dietary assessment, informed public health policies and product innovation. By combining scientific research with traditional knowledge, NUS can contribute to resilient, culturally relevant, and sustainable food systems in Thailand and globally.